The evaluation of a palliative care programme for people suffering from life‐limiting diseases. Issue 1 (17th June 2013) - Chan, Carmen WH; Chui, Ying Yu; Chair, Sek Ying; Sham, Michael MK; Lo, Raymond SK; Ng, Catalina SM; Chan, Helen YL; Lai, David CY
<x xml:space="preserve">Abstract</x> Aims and objectives To report on the effectiveness of an eight‐week palliative care programme in Hong Kong. Background A recent survey reported that the quality of palliative care services in Hong Kong ranked the 20th among 40 countries and it is far behind other Asian countries. There are disagreement and inadequate communication in clinical decision‐making among patients, families and healthcare professionals, and that the nurses lack sufficient knowledge and skills in providing palliative care and advance care planning. Design A pretest post‐test design and semi‐structured interviews were adopted. Methods A total of 108 home care patients with life‐limiting disease and their family caregivers in Hong Kong were recruited to complete a set of questionnaire including The McGill Quality of Life Questionnaire for Hong Kong Chinese and the Family Satisfaction Scale before and after they attended an eight‐week programme. The programme comprised the elements of symptom management, intensive communication on advance care planning and psychosocial intervention. Results Pearson's chi‐square tests and Wilcoxon matched paired tests show a general trend that the patients' quality of life was improved after the programme. Their understanding and active participation in advance care planning was also improved. The hospital readmission rate and the days of hospital stays were significantly reduced. In qualitative interview, four major themes were identified that are as follows: improvement in the communication of treatment plans and after‐death arrangements, symptom management, emotional support and suggested areas of improvement. Conclusion The study supports the benefit of implementing a palliative care programme to patients with life‐limiting disease. Patients demonstrated improved understanding and changed behaviour as regards the preparation for death and dying after the eight‐week programme. Relevance to clinical practice The programme could be replicated in other hospitals and infirmaries that offer home care services.